PENINGKATAN HASIL BELAJAR IPAS MATERI BENTANG ALAM MELALUI PENGGUNAAN MEDIA DIORAMA INTERAKTIF PADA MURID KELAS 3 UPT SD NEGERI LATSARI TUBAN - Nadya Ayu Nathania; Sri Cacik; Novita Dewi (STKIP Subang, 2026)
Learning about landforms in grade 3 of elementary school often presents challenges because it involves physical geographical concepts that are difficult for students to observe directly in their daily lives. This challenge was encountered by students in grade 3C at UPT SD Negeri Latsari Tuban, who experienced difficulties in visualizing the characteristics of various landforms due to the use of conventional teaching methods that were not fully aligned with their cognitive developmental stage. This study aimed to improve students learning outcomes through the use of interactive diorama media in Science and Social Studies lessons on landforms. This research employed Classroom Action Research (CAR) conducted in two cycles. The research subjects were 27 students of grade 3C, consisting of 12 females and 15 males. Data were collected through interviews, observations of student and teacher activities, evaluation sheets, and self-reflection sheets. The results showed that the use of interactive diorama media significantly improved student learning outcomes. The classical mastery percentage increased gradually, starting from 37% in the pre-cycle, 63% in Cycle I, and reaching 100% in Cycle II. This improvement was supported by the achievement of the predetermined success indicator of 75%, with teacher activity reaching 92.5%, student attitude activity reaching 90%, and student skills activity reaching 89%. Based on these results, it can be concluded that the use of interactive diorama media is effective in improving the learning outcomes of Grade 3C students at UPT SD Negeri Latsari Tuban in IPAS on landform materials.